The Influence of Intensity of TikTok Use on Consumer Behavior among Early Adult Hallyu Korean Wave Fans in Padang - Gusri, Putri Yulia Rezki; Free Dirga Dwatra (Causalita, 2024)
The aim of this study is to examine the impact of TikTok usage intensity on consumer behavior among young adults who are fans of the Hallyu Korean Wave. This research employs a quantitative approach using simple linear regression analysis. The sampling technique used is purposive sampling, with a total of 100 young adult respondents who are fans of the Hallyu Korean Wave. Data were collected through questionnaires on TikTok usage intensity and consumer behavior, and analyzed using simple linear regression statistical tests. The statistical analysis results show an r value of 0.581 and an R square value of 33.7%, indicating a significant influence between the independent variable (TikTok usage intensity) and the dependent variable (consumer behavior) with a significance level of 0.000 (< 0.05). Therefore, it can be concluded that a higher intensity of TikTok usage is associated with increased consumer behavior among young adult fans of the Hallyu Korean Wave.